Management of Rumex dentatus L. in Vicia faba L. cultivations via Ononis vaginalis Vahl. As a potential bioherbicide - Roufaida M. Elghobashy; Shimaa A. Rashed; Amal M. Fakhry; Reham M. Mostafa; Heba S. Essawy; Salama M. El-Darier (Heliyon, 2024)
Biological control of undesirable weeds associated with crop cultivation is a sustainable approach that can reduce chemical herbicide dependence. The current study aimed to assess the bio-herbicidal potential of the donor species Ononis vaginalis Vahl. on germination efficiency as well as various growth and physiological parameters of the recipient species Rumex dentatus L., a major broad bean pest (Vicia faba L.). To assess the greatest inhibitory allelopathic effect on the recipient species in mixed (Rumex dentatus L. and Vicia faba L.) and pure cultures (each one separately), two experiments were conducted under laboratory conditions. A Petri dish experiment using O. vaginalis shoot aqueous extract (5%, 10%, 20%, and 40%) and a pot experiment using O. vaginalis shoot crude powder (1%, 2%, 5%, and 10%) were conducted to investigate its biological activity on some growth and physiological parameters of both crop and weed species. O. vaginalis underwent a general phytochemical screening that revealed a high production of allelochemicals, which are secondary metabolites and may have a function like that of natural herbicides. The result showed that the germination of V. faba seeds in both pure and mixed cultures was not significantly affected by low levels of O. vaginalis shoot aqueous extract treatments in pure and mixed cultures, in contrast, those recorded for R. dentatus gradually dropped as levels of O. vaginalis increased in both cultures. Results recorded a significant increase in total phenolics of V. faba shoots and roots under different treatments, except at the high concentrations of crude powder at the donor species level (5 and10%). A reduction in the total phenolic and flavonoid fractions was observed in R. dentatus roots under varying concentration treatments. Conversely, under high concentration treatments, flavonoids decreased in the roots of the mixed culture of R. dentatus but increased in the shoots. In conclusion, allelopathy can be used to suppress weeds in field crops. The study confirmed the use of O. vaginalis into current weed control techniques. O. vaginalis could be explored further for weed suppression in the field.